A case of cavernous skull hemangioma of the frontal bone: Imaging features and diagnostic importance (Indian Journal of Case Reports, 2026)
Skull hemangiomas are rare, benign vascular tumors that account for <1% of all osseous neoplasms. They are typically slow-growing lesions arising from the diploic space of the calvarial bones, most frequently involving the frontal and parietal regions. We present the case of a 40-year-old woman with a painless, gradually enlarging swelling over the right frontal region for 7 years. Computed tomography of the skull revealed a well-circumscribed, expansile, lytic lesion in the diploic space of the right frontal bone, showing thickened trabeculae radiating from a central point, producing a characteristic “sunburst” appearance. The lesion demonstrated homogeneous post-contrast enhancement without evidence of cortical destruction or intracranial extension. Surgical excision was performed for cosmetic reasons, and histopathological examination confirmed the diagnosis of cavernous skull hemangioma. The post-operative course was uneventful, and follow-up imaging revealed no recurrence. Recognition of the distinctive imaging features of skull hemangiomas is essential for differentiating them from aggressive skull lesions and guiding appropriate management.